2021
DOI: 10.1111/ijcp.14566
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve myxoma—A systematic review of published cases

Abstract: Cardiac myxoma is the most common primary cardiac tumour. 1 Cardiac myxomas mostly arise from the mitral valve (75%) and those originating from the aortic valve accounts for ~3% of the cardiac myxomas. [2][3][4] Most of the cardiac tumours are a result of metastasis and they are 30 times more frequent than primary tumours-like aortic valve myxoma. 5 Up to 20% of the myxomas are asymptomatic and 90% of them are located in the left atrium. 6 10% of the cases are associated with Carney syndrome-an autosomal domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Our case of aortic valve myxoma falls under this type, characterized by an irregular, villous surface and a gelatinous texture. Among the 16 aortic valve myxoma cases reviewed by Sachdeva et al [2] and our own case, 64% of them involved at least the right coronary cusp (11/17), and 29% of these cases resulted in ischemic cerebrovascular events (5/17). Our case is the only one who presenting with vision loss and tumors on all three cusps.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Our case of aortic valve myxoma falls under this type, characterized by an irregular, villous surface and a gelatinous texture. Among the 16 aortic valve myxoma cases reviewed by Sachdeva et al [2] and our own case, 64% of them involved at least the right coronary cusp (11/17), and 29% of these cases resulted in ischemic cerebrovascular events (5/17). Our case is the only one who presenting with vision loss and tumors on all three cusps.…”
mentioning
confidence: 50%
“…[1] According to research, up to 25% of patients with aortic valve myxoma experience cerebrovascular events. [2] We are here to present a case of aortic valve myxoma presenting with sudden vision loss and tumors on all three cusps.…”
mentioning
confidence: 99%
“…Indeed, MT-treated AIS secondary to left ventricle myxoma has been reported previously ( 17 ). A recent systematic review on aortic valve myxoma indicated that cerebrovascular events are one of the most common presentations of aortic valve myxoma ( 19 ). Interestingly, Rao et al reported an extremely rare case of recurrent stroke that was the result of a right ventricle myxoma and a patent foramen ovale.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac myxoma is a benign tumor that can grow in four chambers or valves of the heart with a risk of recurrence, and the left atrium is the most likely site for tumor growth. 4,5 Small myxomas of the heart are often asymptomatic, but the larger tumors can lead to hemodynamic abnormalities, which can cause related clinical symptoms, such as chest tightness, orthopnea, breathlessness, cardiac arrest, and other signs of cardiac insufficiency. Myxoma of the heart can also cause embolization of the brain, coronary, visceral organs, and limb arteries due to the embolus detached from the tumor, 6 as well as autoimmune-related symptoms, such as blood abnormalities (decreased antithrombin (ATIII), heparin resistance, anemia, abnormal plasma albumin), fever, urticaria, poor appetite, emaciation, and systemic failure.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac myxoma is a benign tumor that can grow in four chambers or valves of the heart with a risk of recurrence, and the left atrium is the most likely site for tumor growth 4,5 . Small myxomas of the heart are often asymptomatic, but the larger tumors can lead to hemodynamic abnormalities, which can cause related clinical symptoms, such as chest tightness, orthopnea, breathlessness, cardiac arrest, and other signs of cardiac insufficiency.…”
Section: Discussionmentioning
confidence: 99%